A review of the CEO succession management for Yayasan Sabah Group (YSG) / Yamani Hafez Musa, A. Ashar A. Paturusi and Mariam Mujim - Musa, Yamani Hafez; A. Paturusi, A. Ashar; Mujim, Mariam (2012)
The meaning of the word leadership is changing over time, and so is the role of the CEO. Identifying, selecting and recruiting the right leader are known to give the organization a competitive advantage. The objective of this study therefore to gain knowledge in what constitutes as the critical success factors in selecting a CEO for Yayasan Sabah Group (YSG). This study approaches CEO recruitment from both an external and internal perspective through dialogues with recruitment consultants as well as with the YSG Human Resource-Manager. The study further raises the question whether Yayasan Sabah Human Resource Department (YS HRD) could play a more significant role in leadership succession management. This study found character, competence and compatibility as the critical success factors in selecting a CEO and propose the concept of 3C.